A study of bone mineral density among people living with HIV in India and its correlation with CD4 count - Sawlani, Kamal K.; Singh, Sushrut; Chaudhary, Shyam C.; Reddy, D. Himanshu; Usman, Kauser; Atam, Virendera (International Journal of Research in Medical Sciences, 2017)
Background: Data on the prevalence of osteoporosis in HIV patients in Asian population is scarce this study was done to find out the prevalence of osteoporosis in HIV infected patients and its correlation with CD4 counts. Methods: This cross- sectional study was conducted in NACO- ART center of tertiary care hospital. Total 115 HIV patients were included in this study which were divided into ART naive (n= 69) and patients taking ART (n= 46). We analysed BMD by DEXA in 115 HIV positive patients and 78 HIV negative age and sex matched controls. Correlation of BMD with a CD4 count and ART regimen was studied. Results: BMD was found to be low in HIV positive patients. T score in HIV positive patients was significantly lower (p<0.05) as compared to the HIV negative control group. The prevalence of osteopenia and osteoporosis in HIV positive patients was 50.4% and 29.6% respectively, as compared to 23.1% and 2.6% in HIV negative controls. BMD showed relation with CD4 count. We did not find any statistical difference between any ART regimen and BMD. Conclusions: The prevalence of osteopenia and osteoporosis in HIV infected cases was higher as compared to HIV negative controls and higher in ART group as compared to ART naïve group. Low BMD levels show correlation with low CD4 count. We recommend that HIV positive patients especially with advanced stage of disease, low CD4 count should be screened for low BMD by DEXA scan for osteoporosis and managed accordingly